Teachers' Attitudes toward Autism Spectrum Disorder: A Systematic Review - Irene Gómez-Marí; Pilar Sanz-Cervera; Raúl Tárraga-Mínguez (MDPI AG, 2022)
(1) Teachers' attitudes toward the inclusion of students with autism spectrum disorder (ASD) in mainstream schools influence daily educational practices. Depending on whether these attitudes are favorable or not, inclusive education could be fully or partially reached. This systematic review aims to analyze teachers' attitudes toward ASD and to determine the variables that moderate them. (2) We conducted a systematic review in WoS, Scopus, and PsycINFO databases, obtaining an amount of 16 studies included in this review. (3) The results revealed inconclusive levels in teachers' attitudes: Some of the teachers reported positive attitudes, some neutral, and some negative. (4) Among the variables that probably moderate attitudes, we found knowledge, experience, training, and gender. Future research and implications for pre-service and in-service teachers, school administrators, and policy makers are suggested.